Suicide prevention: A qualitative study with Thai secondary school students - Surachai Chaniang; Kamonnat Klongdee; Yupared Jompaeng (Belitung Nursing Journal, 2022)
Background: Suicide is the second leading cause of death among adolescents around the globe. Therefore, understanding its causes and prevention is needed. Objective: This study aimed to explore Thai secondary school students’ perceptions related to causes and preventions of suicide and the learning needs of suicide prevention. Methods: A descriptive qualitative approach was employed in this study. Purposive sampling was used to select 32 adolescents for focus group discussions and ten adolescents for in-depth interviews. Data were collected from September 2019 to March 2020 and analyzed using content analysis.   Results: Causes of suicide included seven sub-categories: parents’ expectations of children’s academic achievement, bullying, family problems, teenage love, lack of stress management skill, imitation behavior on social media, and substance use behavior. Suicide prevention consisted of five sub-categories: peer support, parental support, school support, health professionals and significant support, and knowing the value and believing in self. In addition, students’ learning needs had two sub-categories: developing online learning platforms regarding suicide prevention and mental health promotion and prevention projects. Conclusion: The findings of this study could guide nurses and other health professionals to develop a suicide prevention program for secondary school students. The study results could also be used as essential evidence for driving health care policy in promoting and preventing suicide in adolescents with the involvement of key stakeholders.